علاج كسور الساق المغلقة عند البالغين بأجهزة AO - Sharmak, Yasser Mahmoud (Latakia University Journal -Medical Sciences Series, 2019)
علاج كسور الساق المغلقة عند البالغين بأجهزة AO ياسر محمود شرمك شملت الدراسة 30 مريض لديهم كسر ساق مغلق بمستويات مختلفة عولجوا بأجهزة تثبيت خارجي نوع AO دون فتح البؤرة /عبر الجلد/ بمساعدة جهاز التنظير القوسي في مشفى تشرين الجامعي وذلك في الاعوام 2016/2017 والنصف الاول من 2018 اظهرت الدراسة فعالية تامة لهذه الأجهزة من حيث سرعة التطبيق وقلة الاختلاطات وسرعة الشفاء والاندمال مقارنة بالجراحه التقليدية المفتوحة حيث تم الحفاظ على مصادر تشكل الدشبذ الداخلي (النقوي)والخارجي (السمحاق) دون رض جراحي - Our study was conducted on 30 patients with closed leg fractures and different levels treated with AO external fixation device without opening the trans skin focus with the help of endoscopy devise at Tishreen University Hospital in 2016 and 2017 and first half of 2018. - The study showed the full effectiveness of these devise in terms of speed of application and lack of complications and the speed healing and union compared to tradition of open surgery, where has been preserved sources constitute the internal and external callus myelogenous periosteal without surgical trauma.